ANALISIS KUALITAS PELAYANAN DAN KEPUASAN KONSUMEN DUNKIN DONUTS GADING SERPONG - Abel Gandhy (Politeknik APP Jakarta, 2018)
This study aims to determine service quality and customer satisfaction of Dunkin Donuts customer in Gading Serpong. Service quality are consists of tangible, reliability, responsiveness, assurance, and empathy. Research conducted at Dunkin Donuts Gading Serpong from April-July 2017. Respondents are used as research samples amounted to 100 people. Data were processed by using Index Performance Analysis (IPA) and Customer Satisfaction Index (CSI) method. Overall, the services provided by dunkin donuts outlet in Gading Serpong is good, because they can meet the expectations of their customer. The value of Customer Satisfaction Index (CSI) is 86.76%. This illustrate that Dunkin Donuts customers in Gading Serpong are very satisfied with the service quality performance provided by Dunkin Donuts. Improvement of services that need to be done is the speed of employees in handling customer complaints, improving the cleanliness of toilet facilities, and improving employee friendliness while serving customers